Snow and Leverage - Giroud, Xavier; Mueller, Holger M.; Stomper, Alex; Westerkamp, Arne (Review of Financial Studies, 2012)
Based on a sample of highly leveraged Austrian ski hotels undergoing debt restructurings, we show that reducing a debt overhang leads to a significant improvement in operating performance. Changes in leverage in the debt restructurings are instrumented with Unexpected Snow, which captures the extent to which a ski hotel experienced unusually good or bad snow conditions prior to the debt restructuring. Unexpected Snow provides lending banks with the counterfactual of what would have been the ski hotel's operating performance in the absence of strategic default, allowing them to distinguish between ski hotels that are in distress due to negative demand shocks (“liquidity defaulters”) and those that are in distress due to debt overhang (“strategic defaulters”).